Financial Modernity and Kafa’ah: A Study on the Rising Standards of the Ideal Partner for Generation Z from the Perspective of Islamic Marriage Law (A Study by PT Fajar Paper Wisesa Tbk) - Muhammad Syauqi; Emha Hasan Aminullah (al-Afkar, Journal For Islamic Studies, 2026)
The increasing divorce rate in Indonesia due to economic disharmony has prompted the urgent need for a study on the shift in marriage values among Generation Z. This study aims to analyze the influence of financial modernity on the perception of the ideal partner among Generation Z employees at PT Fajar Paper Wisesa Tbk, as well as to understand the concept of kafa'ah in Islamic marriage law, particularly the financial aspect. The method used is qualitative with a case study approach, conducted in January–February 2026 through in-depth interviews and participatory observation of five key informants who are Muslim employees aged 20–25 years. The results show that financial modernity has reconstructed the ideal partner standard into a financial partnership that prioritizes stable income, investment literacy, and financial technology (fintech) adaptability. Generation Z employees no longer interpret kafa'ah in terms of lineage or descent, but rather in terms of financial competence and career stability. From an Islamic law perspective, this shift is considered relevant because kafa'ah is dynamic in accordance with 'urf, is a manifestation of the al-istitha'ah requirement, and serves to maintain hifzh al-mal and hifzh al-nasl within the framework of maqashid sharia. However, unrealistic standards have the potential to complicate marriage, making sharia financial literacy a crucial solution.